Designing with Generative AI: Nurturing or Numbing Student Creativity? - Wiradarmo, Aulia Ardista (Meraki: Journal of Creative Industries, 2026)
This study examines the integration of text-to-image Generative AI (GenAI) into design education, focusing on its potential to enhance creativity and ideation, as well as its limitations. Conducted with students from two Indonesian universities, the research highlights how GenAI supports design experimentation in culture-inspired works. While GenAI offers valuable ideation support, students encounter challenges with prompt specificity, cultural relevance, and technical accuracy, suggesting that GenAI is more effective as a conceptual tool than as a final design solution. Additionally, although students demonstrate technological readiness, they often overlook ethical considerations, underscoring a need for structured guidance on responsible usage. The findings suggest that incorporating GenAI into design curricula has the potential to support creative exploration by using looser prompts to provoke imagination. However, teachers must assist students in using it to promote ethical awareness and preserve their unique styles.